MEASUREMENT OF LONGSOR LAND VULNERABILITY AS A DIFFICULTY PLAN FOR RESOURCES IN RESOURCES - Muhammad Nursa'ban; Sugiharyanto Sugiharyanto; Nurul Khotimah (Jurnal Penelitian Saintek, 2010)
The objectives of this research are to: Investigating the level of landslide susceptibility and identifying the distribution of landslide   susceptibility locations in Menoreh Mountains area. This is the  explorative research. The subject of this research are Menoreh Mountains  area in Bagelen, and Bener districts Purworejo regency, in addition to Samigaluh District in Kulonprogo Regency. Land units  were chosen as the sample using the purposive area sampling technique.  Thirty land units were obtained by overlay maps of slope, geology,  and soil types. Data collecting  was conducted  with observation method and documentation  to be analyzed by qualitative deskriptif. Findings shown that (I) the level of landslide susceptibility  that is in four  categories in Samigaluh and Bener districts are low, medium, high, and very high.  While three categories were low, medium, and high clasified in Bagelen  district. The distributions of low landslide susceptibility covered about 46.500.527,08 m2 (2 land units in Samigaluh, 3 land units in Bener, and 3 land units in Bagelen). The medium categories covered about  104480073,8  m2 (l land units in Samigaluh,  4 land units in Bener, and 7 land units in Bagelen). High categories covered about 67734399,31 m2 (each of district is 2 land units). The very high categories covered about 12228602,01 m2 (2 land units for both, Samigaluh and Bener District). Key words: landslide, susceptibility,  mitigation, hazard, Menoreh